Tuberous sclerosis complex: a case report and literature review - Yanlin Li; Zhihua Si; Wei Zhao; Cong Xie; Xu Zhang; Ju Liu; Jinzhi Liu; Zhangyong Xia (Italian Journal of Pediatrics, 2023)
Abstract Tuberous sclerosis complex (TSC) is an autosomal dominant disorder with different initial symptoms and complex clinical manifestations. A 14-year-old female patient presented with persistent fever and severe headache. Medical imaging examinations revealed multiple abnormal intracranial lesions. The patient had previously been misdiagnosed with “encephalitis and acute disseminated encephalomyelitis” after visiting numerous hospitals. Eventually, by combing the characteristics of the case and genetic testing results, the patient was diagnosed with TSC accompanied by Mycoplasma pneumoniae infection. The purpose of this case report and literature review is to improve understanding of the clinical diagnosis and treatment of TSC so as to avoid misdiagnosis, missed diagnosis, and overtreatment.